The First Large Absorption Survey in H i (FLASH): I. Science goals and survey design. (21st March 2022) - Allison, James R.; Sadler, E. M.; Amaral, A. D.; An, T.; Curran, S. J.; Darling, J.; Edge, A. C.; Ellison, S. L.; Emig, K. L.; Gaensler, B. M.; Garratt-Smithson, L.; Glowacki, M.; et al.
Abstract: We describe the scientific goals and survey design of the First Large Absorption Survey in H i (FLASH), a wide field survey for 21-cm line absorption in neutral atomic hydrogen (H i ) at intermediate cosmological redshifts. FLASH will be carried out with the Australian Square Kilometre Array Pathfinder (ASKAP) radio telescope and is planned to cover the sky south of δ ≈ +40 at frequencies between 711.5 and 999.5 MHz. At redshifts between z = 0.4 and 1.0 (look-back times of 4 – 8 Gyr), the H i content of the Universe has been poorly explored due to the difficulty of carrying out radio surveys for faint 21-cm line emission and, at ultra-violet wavelengths, space-borne searches for Damped Lyman- α absorption in quasar spectra. The ASKAP wide field of view and large spectral bandwidth, in combination with a radio-quiet site, will enable a search for absorption lines in the radio spectra of bright continuum sources over 80% of the sky. This survey is expected to detect at least several hundred intervening 21-cm absorbers and will produce an H i -absorption-selected catalogue of galaxies rich in cool, star-forming gas, some of which may be concealed from optical surveys. Likewise, at least several hundred associated 21-cm absorbers are expected to be detected within the host galaxies of radio sources at 0.4 < z < 1.0, providing valuable kinematical information for models of gas accretion and jet-driven feedback in radio-loud active galactic nuclei. FLASH will also detect OH 18-cm absorbers in diffuse molecular gas, megamaser OH emission, radio recombination lines, and stacked H i emission.